Air-Coupled Ultrasonic Receivers with High Electromechanical Coupling PMN-32%PT Strip-Like Piezoelectric Elements - Rymantas J. Kazys; Reimondas Sliteris; Justina Sestoke (Sensors, 2017)
For improvement of the efficiency of air-coupled ultrasonic transducers PMN-32%PT piezoelectric crystals which possess very high piezoelectric properties may be used. The electromechanical coupling factor of such crystals for all main vibration modes such as the thickness extension and transverse extension modes is more than 0.9. Operation of ultrasonic transducers with such piezoelectric elements in transmitting and receiving modes is rather different. Therefore, for transmission and reception of ultrasonic signals, separate piezoelectric elements with different dimensions must be used. The objective of this research was development of novel air-coupled ultrasonic receivers with PMN-32%PT strip-like piezoelectric elements vibrating in a transverse-extension mode with electromechanically controlled operation and suitable for applications in ultrasonic arrays. Performance of piezoelectric receivers made of the PMN-32%PT strip-like elements vibrating in this mode may be efficiently controlled by selecting geometry of the electrodes covering side surfaces of the piezoelectric element. It is equivalent to introduction of electromechanical damping which does not require any additional backing element. For this purpose; we have proposed the continuous electrodes to divide into two pairs of electrodes. The one pair is used to pick up the electric signal; another one is exploited for electromechanical damping. Two types of electrodes may be used—rectangular or non-rectangular—with a gap between them directed at some angle, usually 45°. The frequency bandwidth is wider (up to 9 kHz) in the case of non-rectangular electrodes. The strip-like acoustic matching element bonded to the tip of the PMN-32%PT crystal may significantly enhance the performance of the ultrasonic receiver. It was proposed to use for this purpose AIREX T10.110 rigid polymer foam, the acoustic impedance of which is close to the optimal value necessary for matching with air. It was found that in order to get a wide bandwidth the length of the matching strip should be selected not a quarter wavelength λ/4 at the antiresonance frequency but at lower frequency. It allowed achieving the frequency bandwidth (14–18)% with respect to the central frequency at −3 dB level.